Rehabilitation Nursing: differentiation in promoting the autonomy of the elderly - Andreia Maria Lima; Maria Manuela Ferreira da Silva Martins; Maria Salomé Martins Ferreira; Francisco Sampaio; Soraia Dornelles Schoeller; Vítor Sérgio Oliveira Parola (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: The promotion of autonomy, through the use of nursing interventions that promote physical, cognitive and social integration skills, are added competencies of nurses specialized in rehabilitation nursing, so it is important to realize whether these professionals invest in this area in their practices. Objectives: To identify and compare the perception of nurses who are specialists in rehabilitation nursing and nurses who are specialists in other specialty areas. Methodology: A descriptive, correlational, cross-sectional, quantitative study with non-probabilistic snowball sampling. For data collection, the Self-Assessment Scale of Elderly Autonomy was used between September and October 2020. Results: The sample consists of 151 specialist nurses, 72 specialists in rehabilitation nursing, and 79 specialists in other specialty areas. All specialist nurses promote the autonomy of the elderly with less visibility in the development of interventions for instrumental activities of daily living. It is perceived that the nurse specialist in rehabilitation nursing promotes more autonomy of the elderly on a broader scale (p <0.05), with a more significant difference concerning the development of physical and cognitive interventions (<0.001). Conclusion: All specialist nurses perceive that they promote the elderly's autonomy but have weaknesses in interventions that promote instrumental activities of daily living. The specialist nurses in rehabilitation nursing realize that they promote more autonomy for the elderly, probably due to the implementation of rehabilitation programs aimed at this promotion.